Penggunaan Alat Peraga Untuk Meningkatkan Kreativitas Siswa Kelas V Materi Sistem Pernapasan Manusia Di SD Negeri 5 Banda Aceh - yuna salsabila; Ahadin Ahadin; Mislinawati Mislinawati (Elementary Education Research, 2023)
Everything that is used as a tool to help students reinforce new information or skills acquired is called teaching aids. These props can help the learning process. The formulation of the problem in this research is how is the use of visual aids that can increase the creativity of students in class V discussing the human respiratory system at SD Negeri 5 Banda Aceh? The aim of the research is to find out the use of visual aids to increase the creativity of fifth grade students, especially the material on the human respiratory system at SD Negeri 5 Banda Aceh. The approach chosen as the research approach is a qualitative descriptive type. The research was conducted in class V SD Negeri 5 Banda Aceh. The research subjects were 20 students of class V with details of 7 boys and 13 girls. The techniques in collecting data are by means of observation, interviews and documentation. Furthermore, the data was analyzed by data reduction, data presentation and conclusions. The data collected was in the form of student creativity in making teaching aids and their use in the human respiratory system material. As a result of the research, it shows that the use of visual aids to increase students' creativity on the human respiratory system material has improved well. this is evidenced by the value of student creativity, that is, at a very good level, 8 students are obtained, at a good level, 3 students are obtained, at a sufficient level, 7 students, and 2 students need guidance. Therefore, it was concluded that the use of teaching aids was proven to be able to increase the creativity of fifth grade students on the human respiratory system material at SD Negeri 5 Banda Aceh in the good category. Keywords :  Props, Creativity, Human Respiratory System.